Prevalence of Hepatitis B Infection Among Male Prisoners in Malang - Syifa Mustika; Daya Daryadijaya (The Indonesian Society for Digestive Endoscopy, 2019)
Background: Hepatitis B virus (HBV) infection is a global public health problem. Prison populations are at high risk for HBV transmission. In Prison, there is very rare to perfom screening for hepatitis B. This study aims to determine the prevalence of HBV infection among male prisoners in Malang, East Java Province of Indonesia.Method: In this cross sectional study, a total of 165 male prisoners were screened using rapid test (DiaSpot® test kit) for detection of HbsAg in serum samples.Results: The risk factors for HBV transmission were had permanent tattoo (11.32%), multiple sex partner (6.67%), injecting drug users (24.32%), history of blood tranfusion (4.76%), and family history of hepatitis (9.37%). There are 101 subjects (61.2%) for negative anti-HBs result. Positive result for HBsAg and anti-HBs were 7.8% and 30.9% respectively.Conclusion: The prevalence of HBV infection among male prisoners was 7.8%. It is suggested to perfom HBV infection screening on high risk population routinely.